Similar but Not Identical—Binding Properties of LSU (Response to Low Sulfur) Proteins From Arabidopsis thaliana - Niemiro, Anna; Cysewski, Dominik; Brzywczy, Jerzy; Wawrzyńska, Anna; Sieńko, Marzena; Poznański, Jarosław; Sirko, Agnieszka (Frontiers in Plant Science, 2020)
Members of the plant-specific LSU (RESPONSE TO LOW SULFUR) family are strongly induced during sulfur starvation. The molecular functions of these proteins are unknown; however, they were identified as important stress-related hubs in several studies. In Arabidopsis thaliana, there are four members of the LSU family (LSU1–4). These proteins are small (approximately 100 amino acids), with coiled-coil structures. In this work, we investigated interactions between different monomers of LSU1–4. Differences in homo- and heterodimer formation were observed. Our structural models of LSU1–4 homo- and heterodimers were in agreement with our experimental observations and may help understand their binding properties. LSU proteins are involved in multiple protein–protein interactions, with the literature suggesting they can integrate abiotic and biotic stress responses. Previously, LSU partners were identified using the yeast two hybrid approach, therefore we sought to determine proteins co-purifying with LSU family members using protein extracts isolated from plants ectopically expressing TAP-tagged LSU1–4 constructs. These experiments revealed 46 new candidates for LSU partners. We tested four of them (and two other proteins, CAT2 and NBR1) for interaction with LSU1–4 by other methods. Binding of all six proteins with LSU1–4 was confirmed by Bimolecular Fluorescence Complementation, while only three of them were interacting with LSUs in yeast-two-hybrid. Additionally, we conducted network analysis of LSU interactome and revealed novel clues for the possible cellular function of these proteins.